Culture Repertoire in Expressive Written Language : Study of Hypothesis of Edward Sapir and Benyamin Lee Whorf - Alfi Syahrin (BIRCU, 2018)
Language, culture, and mind are closely related, each of these extracts reflects one another. The relationship between language, culture and mind of speakers is a basic idea of Sapir and Whorf's theories and hypotheses. Language politeness that is rooted in the splash of the cultural values of the speaking community, including can be seen from the packaging of the information structure as outlined in the sentence of a language. The construction of different clauses grammatically packs different information structures and politeness values. The way of thinking between cultures as outlined in a writing will be different in the way it is delivered. The purpose of this study is to describe culture in expressive writing, is seen from the hypothesis of Edwar Sapir and Benjamin Lee Whorf.